2010
DOI: 10.1186/1743-7075-7-15
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of oleoyl-estrone and a specific β3-adrenergic agonist (CL316, 243) on the expression of genes involved in energy metabolism of rat white adipose tissue

Abstract: BackgroundThe combination of oleoyl-estrone (OE) and a selective β3-adrenergic agonist (B3A; CL316,243) treatment in rats results in a profound and rapid wasting of body reserves (lipid).MethodsIn the present study we investigated the effect of OE (oral gavage) and/or B3A (subcutaneous constant infusion) administration for 10 days to overweight male rats, compared with controls, on three distinct white adipose tissue (WAT) sites: subcutaneous inguinal, retroperitoneal and epididymal. Tissue weight, DNA (and, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…A peculiarity of OE treatment is the permanent loss of fat, suggesting a role as ponderostat signal for the estrone ester [12]. When OE is given in combination with a ␤ 3 -adrenergic agonist, the WAT wasting effects are markedly increased [13], with additive effects [14]. Similar, but less marked, additive effects were also observed with dexfenfluramine, sibutramine [15] and a thiazolidinedione [16], with opposing effects on WAT lipid integrity, but coincident in maintaining glycemia.…”
Section: Oleoyl-estrone Nature and Effectsmentioning
confidence: 76%
See 2 more Smart Citations
“…A peculiarity of OE treatment is the permanent loss of fat, suggesting a role as ponderostat signal for the estrone ester [12]. When OE is given in combination with a ␤ 3 -adrenergic agonist, the WAT wasting effects are markedly increased [13], with additive effects [14]. Similar, but less marked, additive effects were also observed with dexfenfluramine, sibutramine [15] and a thiazolidinedione [16], with opposing effects on WAT lipid integrity, but coincident in maintaining glycemia.…”
Section: Oleoyl-estrone Nature and Effectsmentioning
confidence: 76%
“…This increase is largely due to adrenal hypertrophia and increased expression of the entire corticosteroid synthetic pathway [23] but is also due to increased liver corticosteroid disposal via 5␣-reductase [22]. Treatment with OE reduces the WAT expression of most cytokines [5,14], especially leptin [5]. The expression of adiponectin is also decreased by OE [14].…”
Section: Oleoyl-estrone Nature and Effectsmentioning
confidence: 95%
See 1 more Smart Citation
“…It was previously suggested that b 3 -adrenoceptor, the predominant subtype of adrenoceptor expressed mainly in white and brown adipose tissue play an important role in the regulation of lipolysis, thermogenesis and energy homeostasis. Earlier studies reported that b 3 -adrenergic receptor stimulation in rats and mice fed high-fat diets is very effective in normalization of obesity [20,21]. Moreover, 4 weeks treatment of obese Zucker rats with CL 316,243 resulted in an increase metabolic rate by 96% per rat as well as in decrease and remodeling of retroperitoneal white fat depots [33].…”
Section: Discussionmentioning
confidence: 94%
“…It was shown that long--term administration of CL 316,243 (CL), a highly selective b 3 -adrenoceptor agonist, largely reduced fat stores and retarded the development of obesity in young rats fed a high-fat diet [18], as well as reversed established diet-induced obesity in older animals [19][20][21]. Similar fat-reducing effect of CL was also described in adult non-obese rats [22,23].…”
Section: Introductionmentioning
confidence: 82%